Teatro filosófico: uma concepção de filosofia à luz de Michel Foucault - Pires Neto, Luiz de Camargo (2018)
Michel Foucault (1926-1984) is a thinker well recognized for establishing a peculiar relationship with philosophy: he constantly affirms that he cannot be considered a philosopher, criticizes the way that philosophy is exercised, rigorously and creatively proposing another form of practicing it. Interested in understanding the transformations of thought, he investigates the past to diagnose the present, invents concepts, constructs ideas, and destroys evidences. Passionate to novelty and always willing to take risks, he develops his intellectual trajectory in search of new ways of acting and thinking. This paper investigates a conception of philosophy in the light of Michel Foucault. Using the resource of metaphor, this conception is presented as a philosophical theater. In “The stage of philosophy”, Foucault states that his life is dedicated to "the theater of truth", a "story of the scene", a story of how sickness, madness and crime were staged. On the other hand, the inventiveness of the Foucauldian thought evokes the vitality of the theatrical performance. In the first chapter the relations between Foucault and the theater appear. The next three chapters summon the theatrical stage as an epistemic and heterotopic space of the philosophy, the actor as a professor, engaged philosopher, endowed with philosophical gestures, and the staging as "radical journalism", diagnosis of the present, "impatience of freedom", transgressive and limit-experience. Facing all these relations, to conceive philosophy as a philosophical theater, means to signalize the possibility of "thinking differently than one thinks, and perceiving differently from what one sees"